Cognitive Performance of Severely Hearing-impaired Older Adults Before and After Cochlear Implantation: Preliminary Results of a Prospective, Longitudinal Cohort Study Using the RBANS-H. Issue 9 (October 2018) - Claes, Annes J.; Van de Heyning, Paul; Gilles, Annick; Van Rompaey, Vincent; Mertens, Griet
Abstract : Objective: To evaluate cognitive change in severely hearing-impaired older adults after cochlear implantation. Study Design: Prospective, longitudinal cohort study with assessments before, and at 6 and 12 months after implantation. Patients: Twenty older adults (median age: 71.5 yr). Main Outcome Measures: Change in the Repeatable Battery for the Assessment of Neuropsychological Status for Hearing-impaired individuals (RBANS-H) total score and subdomain scores were used to assess cognitive evolution. In addition, change in best-aided speech audiometry in quiet (monosyllabic words) and in noise (Leuven Intelligibility Sentences Test [LIST]) was examined, as well as patient-reported measures of health-related quality of life (Nijmegen Cochlear Implant Questionnaire [NCIQ]), self-perceived hearing disability (Speech, Spatial, and Qualities of hearing Scale—12 [SSQ12]), sound quality (Hearing Implant Sound Quality Index—19 [HISQUI19]), and states of anxiety and depression (Hospital Anxiety and Depression Scale [HADS]). Results: The RBANS-H total scores improved significantly after 12 months cochlear implant (CI) usage ( p  < 0.001). At subdomain level, significant improvements were observed in the immediate and delayed memory domain ( p  = 0.005 and p  = 0.002, respectively), and to a lesser extent also in the attention domain ( p  = 0.047). Furthermore, speech perception in quiet and in noise improved significantly after 6 months and remained stable after 12 months. Similarly, a significant improvement was observed on all patient-reported measures after 6 months of CI usage. These results remained stable after 12 months, except for the HADS. Conclusions: A significant improvement in overall cognition after 12 months of CI usage was established. However, future research is imperative to further disentangle possible practice effects from the effects of the cochlear implantation. The significant, positive effect of cochlear implantation on speech perception and patient-reported measures was confirmed.